Implikasi Kebijakan Ekonomi Politik Global Terhadap Pemberdayaan Perempuan di Negara Berkembang - Varga Setyawananda; Firna Putri Az Zahara; Jumita Anggeraini (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
This research aims to analyze the implications of global political economy policies on women's empowerment in developing countries, especially in terms of access to economic resources, education, employment, and political participation. The research uses a literature review method by collecting and analyzing various academic references and relevant public policies to provide a comprehensive understanding of gender issues in the context of globalization. The results show that despite the existence of various affirmative policies such as women's quotas in parliament and economic programs for women, their implementation still faces various structural barriers, including patriarchal culture, limited resources, and low participation of women in decision-making. Other challenges include unequal access to education and training, and social stereotypes that hinder women's advancement. Proposed strategies include integrating gender analysis in policy formulation, increasing women's participation in strategic positions, strengthening regulations that protect women's rights, and gender-sensitive international cooperation. This research confirms the importance of a collaborative and sustainable approach involving various stakeholders to realize inclusive women's empowerment and real gender equality in developing countries.